An introduction to the geography of tourism - Nelson, Velvet, 1979- (Lanham, Maryland : Rowman & Littlefield, 2021)
"Tourism is an astonishingly complex phenomenon that is becoming an ever-greater part of life in today's global world. This clear and engaging text introduces students to this vast and diverse subject through the lens of geography, the only field with the breadth to consider all of the aspects, activities, and perspectives that constitute tourism"--
Includes bibliographical references and index.
Keywords: Tourism -- Environmental aspects; Geographical perception